2011
DOI: 10.1007/s10706-011-9405-1
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Reliability Analysis Applied to Slope Stability: A Case Study From Sungun Copper Mine

Abstract: Nowadays, there are many new methods for slope stability analysis; including probabilistic methods assessing geotechnical uncertainties to develop safety factors. In this paper, a reliability index analysis for the Sungun copper mine slope stability is evaluated based on three methods of uncertainties consisting Taylor series method, Rosenblueth point estimate method and Monte-Carlo simulation method. Sungun copper mine will be one of the Iran's biggest mines with final pit's height of 700 meters. For this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The LandslideProbability component is written in Python and implemented with a model driver (written as a Jupyter Notebook) using the workflow shown in Fig. 1 of the component's user manual (Strauch et al 2018 (Malkawi et al, 2000) to > 1200 (Abbaszadeh et al, 2011) was found to be sufficient in the literature. We used 3000 in this study.…”
Section: Model Development In Landlabmentioning
confidence: 99%
See 1 more Smart Citation
“…The LandslideProbability component is written in Python and implemented with a model driver (written as a Jupyter Notebook) using the workflow shown in Fig. 1 of the component's user manual (Strauch et al 2018 (Malkawi et al, 2000) to > 1200 (Abbaszadeh et al, 2011) was found to be sufficient in the literature. We used 3000 in this study.…”
Section: Model Development In Landlabmentioning
confidence: 99%
“…• in other studies (e.g., Abbaszadeh et al, 2011;Arnone et al, 2016a). Other spatial soil and vegetation datasets can be used in the preprocessing of the model.…”
Section: Model Drivermentioning
confidence: 99%
“…Once the component has been instantiated, the component's method calculate_landslide_probability() is executed in a for loop that performs the calculations at each node. An iteration number in the range of 700 (Malkawi et al, 2000) to > 1200 (Abbaszadeh et al, 2011) was found to be sufficient in the literature. We used 3000 in this study.…”
Section: Model Development In Landlabmentioning
confidence: 92%
“…3.2.1 for details). The current model design assumes negligible correlation between C and ∅ as assumed in other studies (e.g., Abbaszadeh et al, 2011;Arnone et al, 2016a). Other spatial soil and vegetation datasets can be used in the preprocessing of the model.…”
Section: Model Development In Landlabmentioning
confidence: 99%
“…New attempts have been made to apply the PEM [12,13] and by FOSM method [14,15] in slope stability. Recent researches have been made to apply FORM method in slope stability [16].…”
Section: Methodsmentioning
confidence: 99%